Opposite decadal atmospheric trends in the Southern Hemisphere between winter and summer - 胡永云 (2006)
The atmosphere demonstrates noticeable trends in the past few decades. In the present work, we study the decadal trends in the Southern Hemisphere between winter months (June-October) and summer months (December-April) over 1979-2005 using NCEP/NCAR, NCEP/DOE, and ECMWF reanalysis. It is found that . 0